Między "romansem tajemnic" a powieścią społeczną. Wokół wybranych elementów prozy Józefa Dzierzkowskiego = Between the Mystery Novel and the Social Novel - Selected Prose by Joseph Dzierzkowski - Ruszczyńska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The novels by Joseph Dzierzkowski belong to literary achievements that have been, to a large extent,nowadays forgotten. Analysing the pattern of the novel by E. Sue, "The Mysteries of Paris", detectablein the Polish author`s works, the author of this article addresses three novels: "The Jugglers, Fora dowry" and "The drawing room and the street". These connections to a "mystery novel" are visible in the way the municipal space is utilized. In Dzierzkowski`s novels, the city of Lvov, contrary to thefunction of a city in the works by the French author, does not play the role of a rightful character.
Keywords: Dzierzkowski, Józef (pisarz; 1807-1865); literatura polska - historia - 19 w.; powieść polska - 19 w.